1986
DOI: 10.1161/01.str.17.3.377
|View full text |Cite
|
Sign up to set email alerts
|

Stroke unit care--who benefits? Comparisons with general medical care in relation to prognostic indicators on admission.

Abstract: SUMMARY The clinical outcome in 110 patients admitted to a non-intensive stroke unit was compared to that in 183 patients treated for acute stroke in general medical wards. At entry, the two groups of patients were closely similar in all prognostic indicators. Subsets of patients were analyzed in an attempt to identify groups that benefit more than others from stroke unit care.The stroke unit regime had little effect on short-term and long-term mortality rates in the entire stroke population as well as in subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
4

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 7 publications
2
24
0
4
Order By: Relevance
“…This constitutes a paradox because studies have shown that older stroke patients, who generally have a poor clinical prognosis, benefit more from active medical care than younger patients. 29 Stroke management appears to be one of the most important modifiable prognostic factors in older patients, and we believe that a special effort must be made to improve medical care in this older age group.…”
Section: Olindo Et Al Acute Stroke In Very Elderlymentioning
confidence: 98%
“…This constitutes a paradox because studies have shown that older stroke patients, who generally have a poor clinical prognosis, benefit more from active medical care than younger patients. 29 Stroke management appears to be one of the most important modifiable prognostic factors in older patients, and we believe that a special effort must be made to improve medical care in this older age group.…”
Section: Olindo Et Al Acute Stroke In Very Elderlymentioning
confidence: 98%
“…Subgroup analyses were performed for patients with mild, moderate, and severe stroke (Barthel Index of 50 to 100, 15 to 45, and 0 to 10, respectively, during the first 3 days) and for patients with cardiac disease. 1,33 All results were analyzed according to the intention-to-treat principle. Differences between groups in the proportion of patients at home, deceased, or dependent were compared with the use of the Fisher exact test.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…São apresentandas na Tabela 3, as indicações de acordo com os níveis tensionais, para o uso de cada uma delas, baseando-se em protocolos de alguns estudos, particularmente o da American Heart Association (AHA) 7,12,15 . Ao contrário de alguns autores 24,25 , acreditamos que a nifedipina não deve ser usada, devido a sua resposta hipotensiva abrupta 15 . Deve-se ter especial atenção com a hidralazina, tendo em vista a dificuldade de se prever a intensidade do seu efeito 7 .…”
Section: Discussionunclassified
“…Alguns estudos têm mostrado que as "stroke units" reduzem os índices de morbidade e de mortalidade precoce, além de serem economicamente vantajosas, quando comparadas ao tratamento na enfermaria 20,24,25 .…”
Section: Tas < 180unclassified